Cardiac Shock Wave Therapy in Coronary Artery Disease: A Systematic Review and Meta-Analysis - Qiu, Quan; Chen, Shenjie; Qiu, Yuangang; Mao, Wei (Frontiers in Cardiovascular Medicine, 2022)
Objective: Coronary artery disease (CAD) has been one of the leading causes of morbidity and mortality worldwide. Cardiac shock wave therapy (CSWT) is a novel and noninvasive therapy for CAD. Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy of CSWT on CAD. Methods and Results: We performed a comprehensive search of the electronic databases PubMed, EMBASE, the Cochrane Library and Wanfang through October 2021.Results were reported as weighted mean difference (WMD) with 95% confidence interval (CI). Statistical heterogeneity scores were assessed with the standard Cochran’s Q test and the I2 statistic. A total of 8 randomized trials and 2 prospective cohort studies, together involving 643 patients (n = 336 CSWT and n = 307 control), were included in our study. Eight studies with 371 patients showed rest left ventricular ejection fraction (LVEF) was significantly improved after CSWT, as compared to the control group (WMD 3.88, 95%CI 1.53 - 6.23, p = 0.001, I2 = 51.2%). Seven studies with 312 patients reported left ventricular internal diameter in diastole (LVIDd) was markedly decreased in CSWT group compared to the control group (WMD -1.81, 95%CI -3.23 - -0.39, p = 0.012, I2 = 20.3%). Summed stress score was significantly favor CSWT group (WMD -3.76, 95%CI -6.15 - -1.37, p = 0.002, I2 = 56.8%), but there was no significant difference for summed rest score. Our data were acquired from studies without perceived high risk of bias, so plausible bias is unlikely to seriously affect the main findings of the current study. Conclusions: Based on the present meta-analysis of these studies, we could conclude that CSWT could moderately improve myocardial perfusion and cardiac function in patients with CAD. CSWT is meaningful and bears substantial value in clinical practice. Registration: The meta-analysis was registered on OSF (https://osf.io/r2xf9).